Design, synthesis, and duplex-stabilizing properties of conformationally constrained tricyclic analogues of LNA. Issue 6 (14th January 2016) - Giacometti, Robert D.; Salinas, Juan C.; Østergaard, Michael E.; Swayze, Eric E.; Seth, Punit P.; Hanessian, Stephen
Abstract : The design, synthesis and biophysical evaluation of two highly-constrained tricyclic analogues of locked nucleic acid (LNA), which restrict rotation around torsion angle γ are reported. Abstract : The design, synthesis and biophysical evaluation of two highly-constrained tricyclic analogues of locked nucleic acid (LNA), which restrict rotation around the C4′–C5′-exocyclic bond (torsion angle γ ) and enhance hydrophobicity in the minor groove and along the major groove, are reported. A structural model that provides insights into the sugar–phosphate backbone conformations required for efficient hybridization to complementary nucleic acids is also presented.